Feasibility and geotechnical design of subsurface dams in dry ephemeral rivers for the augmentation of shallow groundwater supply - Du Preez, Daniell (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.